Synthesis And Characterization Of Carbon Nanotube Prepared Using Microwave Oven For Hydrogen Gas Sensing Application - Algadri, Natheer Ali (2018)
Carbon nanotubes (CNTs) have garnered substantial interest because of their distinctive electrical, mechanical, thermal, chemical and magnetic properties. However, the requirements for majority of the existing synthesis methods include high temperature or a high vacuum environment. Thus, there is the need for a simpler and low cost method for synthesizing CNT. This study characterize the morphology and optical properties of CNTs synthesized using microwave oven. CNT based hydrogen gas sensors were then fabricated on silicon oxide and glass substrates using a simple and cost-effective deposition method.